Knowledge about Byssinosis and the Use of Face-Masks - Titik Respati; Ganang Ibnusantosa; Meike Rachmawati (Universitas Islam Bandung, 2013)
The development of textile industry in Indonesia can potentially increase some occupational diseases that caused by waste products. One of those waste products from textile industry is cotton dust, which can cause byssinosis. There are several ways to reduce cotton dust exposure, such as using face mask. This research aim to describe the relationship between employee’s knowledge about byssinosis with face mask utilization in spinning department of a textile factory. This research is a descriptive study with cross sectional approach. The subjects of this research are employees working on Spinning Department. Data gathered using questionnaire about byssinosis and the habit of using face mask. The result of this research shows that 52 (79%) of 66 respondents have excellent knowledge about byssinosis, meanwhile the other 14 (21%) show just enough knowledge. Almost all wear a face mask during working hour (92%). The result of chi-square method showed that the relation between employee’s knowledge about byssinosis and face mask utilization was really weak (p=0.001, contingency coefficient=0.381). The result of this research indicates that besides knowledge of byssinosis, there are other factors that can affect face mask utilization. PENGETAHUAN MENGENAI BISINOSIS DAN PEMAKAIAN MASKERPerkembangan industri tekstil di Indonesia berpotensi meningkatkan beberapa penyakit akibat kerja yang diakibatkan oleh buangan hasil industri. Salah satunya adalah debu kapas yang dapat menyebabkan bisinosis. Terdapat beberapa cara untuk mengurangi paparan terhadap debu kapas ini antara lain dengan menggunakan masker. Penelitian ini bertujuan untuk menggambarkan hubungan antara pengetahuan pekerja mengenai bisinosis dengan penggunaan masker pada departemen spinning sebuah pabrik tekstil. Penelitian ini adalah penelitian deskriptif dengan pendekatan cross-sectional. Subjek penelitian ini adalah pekerja pada sebuah pabrik tekstil di bagian spinning. Data dikumpulkan dengan menggunakan kuesioner mengenai bisinosis dan kebiasaan menggunakan masker. Hasil penelitian menunjukkan bahwa 52 orang (79%) dari 66 responden mempunyai pengetahuan yang sangat baik mengenai bisinosis, sedangkan sisanya hanya mempunyai pengetahuan yang cukup. Hasil dari perhitungan statistik menggunakan chi-kuadrat menunjukkan kekuatan hubungan antara pengetahuan mengenai bisinosis dan penggunaan masker sangat lemah (p=0,001, contingency coefficient=0,381). Hasil ini menunjukkan bahwa terdapat faktor lain yang memengaruhi penggunaan masker selain pengetahuan megnenai bisinosis.